Sequence diversity in the coat proteins of Papaya ringspot virus isolates originating from different locations in India - and R.K. JAIN*, S. BAG, SUREKHA AGARWAL (Indian Phytopathology, 2007)
Diversity in Papaya ringspot virus (PRSV) isolates was determined by analyzing amino acid sequences of coat protein of 28 isolates originating from five different geographical locations. PRSV isolates from central, eastern, northern, southern and western India were highly heterogeneous in CP length (275-289 amino acids) and amino acid sequences (up to 23%). Among all the isolates, KA4, INU-01 and AP2 from southern India were unique. Maximum heterogeneity was observed in southern isolates (up to 23%), followed by central (up to 11%), eastern and northern (up to 10%)and western (up to 7%) isolates. Though PRSV isolates were grouped into three clusters, there was lack of relationship between variability and geographical origin of the isolates. The present study suggests that location - specific strategy may have to be developed to manage PRSV.